Ethnic Identity as a Cultural Safety Resource of Local Communities in the Context of Globalization - Igosheva, Marina A.; Paliy, Irina G.; Krolman, Marianna L.; Takhtamyshev, Vladimir G.; Kasyanov, Valery V. (Journal of History Culture and Art Research, 2019)
In the context of globalization, the main threat to the cultural security of local communities is the spiritual expansion of Western civilization, which results in changes in the worldview and lifestyle of people. Under the threat of spiritual expansion, they activate protective mechanisms in order to preserve, reproduce, and transmit cultural norms and values that serve as spiritual guidelines in social uncertainty and global chaos. The ethnic identity, being one of these mechanisms, has the capacity to ensure the ontological security of the community, preserve its cultural identity and mobilize it for positioning and defending its interests. The constructivist paradigm serves the methodological basis of the study and allows considering the ethnic identity as a way of organizing the socio-cultural existence of community on the basis of its "symbolic" boundaries’ identification. The transformational approach which makes it possible to characterize the processes of the modern world and their impact on local societies is methodologically significant for the study. The concept of "socio-cultural crisis", manifested in the destruction of the value-semantic and symbolic world of ethnic communities is conceptual to identify the destructive influence of globalization processes on the life of local communities. The riskological approach allows revealing the specifics of the current risks to the cultural safety of local communities. The study concludes that under the risks and threats to the cultural security of local communities, they activate the resource potential of ethnic identity, which allows maintaining their personal integrity and socio-cultural uniqueness. The resource potential of ethnic identity makes it possible to act as a social behavior regulator and ensure the cultural security of both individuals and groups, forming symbolic boundaries between the worlds of "us" and "them".